THE ANALYSIS OF EXTERNAL FACTORS THAT INFLUENCE LEARNING DIFFICULTY IN LEARNING MATHEMATICS FOR GRADE 4 STUDENTS OF SD NEGERI 125 PEKANBARU - Evi Dwinta Wulandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by a number of students who have difficulty in learning mathematics caused by external factors, including: the attention of family members when learning mathematics, the teacher's method of teaching mathematics, the atmosphere of the home environment, and so on. External factors are very influential on students besides the genetic factors or internal factors. Various problems caused by the stimuli from outside individuals make students experience learning difficulties. This research used descriptive quantitative method that aimed to find out any external factors that affect learning difficulties in learning mathematics for fourth grade students of SD Negeri 125 Pekanbaru. The population of this study consisted of 44 students, with students who received grades below the KKM of 37 students as the sample. Data collection techniques used were documentation and questionnaires. Based on research findings, the external factors influenced the difficulty of learning mathematics for fourth grade students of SD Negeri 125 Pekanbaru. The biggest factor in influencing difficulties in learning mathematics was the teacher's method of teaching mathematics with a percentage of 17.5%.